2021
DOI: 10.1021/acs.jpcc.1c06063
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Decomposition of Dimethyl Methylphosphonate on Size-Selected Zirconium Oxide Trimer Clusters

Abstract: In recent years, zirconium hydroxide powder and zirconium-based metal organic frameworks have found promising applications as chemical warfare agent (CWA) decomposition materials. While bulk zirconium oxide (ZrO2) has proven to be relatively inactive for such purposes, well-controlled fundamental studies investigating the potential CWA decomposition propensity of subnanoscale zirconium oxide, in which undercoordinated metal centers abound, are still severely lacking. Herein, the adsorption and decomposition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 93 publications
1
6
0
Order By: Relevance
“…P2p1 exhibits a 2p 3/2 binding energy of 133.9 eV, which is typical of molecularly chemisorbed DMMP. This has been observed in previous studies of ours, as well as the work of others. , P2p2 exhibits a lower 2p 3/2 binding energy of 132.9 eV, which has been previously assigned to surface-bound phosphonate or phosphate decomposition products. , This result shows that DMMP has already begun to decompose by room temperature and is similar to the results of our previous experiments involving room-temperature exposure of (ZrO 2 ) 3 clusters to DMMP …”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…P2p1 exhibits a 2p 3/2 binding energy of 133.9 eV, which is typical of molecularly chemisorbed DMMP. This has been observed in previous studies of ours, as well as the work of others. , P2p2 exhibits a lower 2p 3/2 binding energy of 132.9 eV, which has been previously assigned to surface-bound phosphonate or phosphate decomposition products. , This result shows that DMMP has already begun to decompose by room temperature and is similar to the results of our previous experiments involving room-temperature exposure of (ZrO 2 ) 3 clusters to DMMP …”
Section: Resultssupporting
confidence: 91%
“…It was found that DMMP was strongly adsorbed by the clusters and proceeded to decompose with heating, evolving primarily methanol along with relatively minor amounts of dimethyl ether and formaldehyde. 28 While the use of small metal oxide particles and clusters as active decomposition species has been a research focus for some time now, a recently emerging newer focus is on the potential application of single catalytically active metal atoms supported on the surface of metal oxide particles to this problem. Over the last decade, the concept of such a single atom catalyst (SAC) was convincingly demonstrated in a seminal study by Qiao et al 29 and spawned a field that has grown exponentially in scope since.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The P 2p spectrum for the nanopowder and mesoporous samples after GB exposure (Figure a) effectively resemble each other. Only a component centered at around 133 eV appears in the P 2p spectrum, commonly observed for GB or DMMP (a simulant for GB) adsorption. ,,, Figure b displays the F 1s spectrum. Two characteristic components appear in the F 1s region for both samples after GB dosing.…”
Section: Results and Discussionmentioning
confidence: 98%
“…This work was conducted using a newly constructed apparatus with substantial improvements over its predecessor, the latter of which was used in previously published work from our laboratory and described in detail previously . The cluster ion beamline was completely redesigned, and the cluster deposition/surface analytical region of the apparatus underwent significant modification, while retaining much of the same analytical instrumentation.…”
Section: Experimental Methodsmentioning
confidence: 99%